Optimal subsidy policy for accelerating the diffusion of green products - Hongguang Peng (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: We consider a dynamic duopoly market in which two firms respectively produce green products and conventional products. The two types of product can substitute each other in some degree. Their demand rates depend on not only prices but the consumers' increasing environmental awareness. Too high initial cost relative to conventional products becomes one of the major obstacles that hinder the adoption of green products. The government employs subsidy policy to trigger the adoption of green products. The purpose of the paper is to explore the optimal subsidy strategy to fulfill the government's objective. Design/methodology/approach: We suppose the players in the game employ open-loop strategies, which make sense since the government generally cannot alter his policy for political and economic purposes. We take a differential game approach and use backward induction to analyze the firms' pricing strategy under Cournot competition, and then focus upon a Stackelberg equilibrium to find the optimal subsidy strategy of the government. Findings: The results show that the more remarkable the energy or environmental performance, or the bigger the initial cost of green products, the higher the subsidy level should be. Due to the increasing environmental awareness and the learning curve, the optimal subsidy level decreases over time. Research limitations/implications: In our model several simplifying assumptions are made to keep the analysis more tractable. In particular, we have assumed only one type of green product. In reality several types of product with different energy or environmental performances exist. Our research can be extended in future work to take into account product differentiation on energy or environmental performance and devise a discriminatory subsidy policy accordingly. Originality/value: In the paper we set the objective of the government as minimizing the total social cost induced by the energy consumption or environmental side effect and government expenditure. In addition, we assume the price of conventional products is variable and examine the Cournot competition between the two firms. This study can provide more valuable managerial insights into improving the design of subsidy policy.
Keywords: 650; price subsidy; Cournot competition; open-loop Stackelberg game; differential game